Traum-A-Rhythmia On Debbie Tucker Green’s In-Yer-Ear Stage - Lea Sawyers (Sillages Critiques)
In an aesthetics of trauma, debbie tucker green gives voice to marginalized and politically minor voices which she directs in her writing as one would a symphonic orchestra. Her texts, which draw simultaneously from poetry, song lyric writing and musical score, question the nature of theatre. As a black woman, writing black characters for a mainly white audience, the strategies of dramatic composition which she resorts to rely on a poetics of absence and create a theatre immune to accusations of didacticism of which her forbearers were often taxed. Indeed, the representation of the public political debate is strikingly absent of tucker green’s otherwise highly politicized stage. AIDS, genocides, domestic violence, incest, civil wars, public executions are all accessed through the prism of deeply personal subjective human experience. Characters on tucker green’s stage see their subjecthood caught in an “in-between”. Neither straightforwardly spectral, nor entirely anchored in an unambiguous dramatic situation, the subject is approached through stereophony as each spectator is confronted to their feelings of empathy and left to negotiate their own hermeneutic path between solo melodies and choral symphonies, between a highly contextualized understanding of the play, and universal reading of the performance. Paradoxically, debbie tucker green therefore redefines 21st century In-yer-face theatre through absence. At odds with the visual frontality of Sarah Kane or Mark Ravenhill, the playwright’s writing focuses its provocative potency on the ear. Characters on stage bleed, tear at each other and love passionately, but most of the drama takes place in and through the language they use. Armed with silence and the weight of the unsaid, tucker green carves a musical score haunted by ghost melodies produced by compositional techniques akin to musical counterpoint, arpeggios and the canon. This paper proposes a reflection on the political consequences of such patterns. What are the terms of the representations of trauma on tucker green’s In-yer-face stage and what part does musicality play in the poetics and politics of such representations?